NIPPONOTROPHON MAKASSARENSIS, A NEW RECENTLY DREDGED MURICACEAN SPECIES OF STRANGE GENERIC AFFINITIES (GASTROPODA: MURICIDAE) - Houart, Roland (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1984)
A murieid, dredged by the French-Indonesian